The Influence of Organizational Commitment, Work Flexibility and Work Load on Employee Performance with Innovative Work Behavior as an Intervening Variable at PT. Ruang Raya Indonesia - Kusumaningrum, Sari Dewi; Andjarwati, Tri; Nugroho, Riyadi (Indonesian Journal Economic Review (IJER), 2025)
PT. Ruang Raya Indonesia (Ruangguru) is the largest technology company in Indonesia that focuses on education-based services. Ruangguru develops various technology-based learning services, including virtual classroom services, online platform tests, subscription learning videos, private tutoring marketplaces, and other educational content that can be accessed through the Ruangguru website and application. Ruangguru has a mission to provide and expand access to quality education through technology for all students, anytime and anywhere, and also aims to improve the quality of teachers by creating jobs and additional income for teachers in Indonesia. Ruangguru believes that by improving the quality of teachers, the quality of education in Indonesia will also improve, and is determined to continue to develop our services and collaborate with various parties to achieve the desired goals. The purpose of this study was to determine the effect of organizational commitment, work flexibility, and workloadon employee performance with innovative work behavior as an intervening variable at PT. Ruang Raya Indonesia. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The research population is employees of PT. Ruang Raya Indonesia. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 93 respondents. The data analysis method uses descriptive analysis and SEM-PLS analysis. The results of the study indicate that the variables of organizational commitment, work flexibility, and workloadaffect employee performance with innovative work behavior as an intervening variable at PT. Ruang Raya Indonesia.